Implementasi Skin Wrap Method Pada Bayi Berat Lahir Rendah Di Ruang Perinatologi RSD Balung Jember - Putri Mz, Nuril Izza Afqorina; Putri, Resti Utami (Jurnal Ilmiah Wahana Pendidikan, 2025)
Low Birth Weight (LBW) babies experience various health problems and are very susceptible to various diseases that can reduce their immune system. LBW babies can experience problems in growth, a risk of cognitive deficits, suboptimal development, behavioral problems, motor delays, and cerebral palsy, so it is easy to experience changes in body temperature such as hypothermia. Hypothermia is one of the complications that occurs in LBW, where the body temperature decreases below 36.5 °C. To prevent hypothermia in low-birth-weight (LBW) babies by implementing the skin wrap method in the perinatology room at RSD Balung Jember. Data collection was carried out by means of interviews, observations, physical examinations, documentation studies, and providing nursing care for LBW by implementing the Skin Wrap Method. Implementation of the Skin Wrap Method was carried out for 2 hours in the morning, from July 8, 2024, to July 10, 2024. The evaluation was carried out on the third day. The results obtained from the implementation of the Skin Wrap Method show that before implementation, the baby's body temperature was 36.2°C, and after implementation, the body temperature increased to 36.4°C. Implementation of the Skin Wrap Method can increase LBW body temperature by up to 0.3°C after treatment for 3x24 hours